2019
DOI: 10.1111/jpi.12593
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppresses milk fat synthesis by inhibiting the mTOR signaling pathway via the MT1 receptor in bovine mammary epithelial cells

Abstract: Milk fat content is an important criterion for assessing milk quality and is one of the main target traits of dairy cattle breeding. Recent studies have shown the importance of melatonin in regulating lipid metabolism, but the potential effects of melatonin on milk fat synthesis in bovine mammary epithelial cells (BMECs) remain unclear. Here, we showed that melatonin supplementation at 10 μmol/L significantly downregulated the mRNA expression of lipid metabolism–related genes and resulted in lower lipid drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…A classic mTOR activator named MHY1485 was applied to validate the internal route of CRYAB commanding M2 polarization in vitro 24,25 . In CRYAB low-expression groups, M2 markers, Akt1/mTOR pathway and phosphorylation of pivotal downriver transcription factors, were declined ( Fig.…”
Section: Trigger Of Akt1/mtor Was Engaged In Cryab-inducing M2 Polarimentioning
confidence: 99%
“…A classic mTOR activator named MHY1485 was applied to validate the internal route of CRYAB commanding M2 polarization in vitro 24,25 . In CRYAB low-expression groups, M2 markers, Akt1/mTOR pathway and phosphorylation of pivotal downriver transcription factors, were declined ( Fig.…”
Section: Trigger Of Akt1/mtor Was Engaged In Cryab-inducing M2 Polarimentioning
confidence: 99%
“…In this study, we observed that melatonin decreased milk fat content in different seasons, ages and lactation periods. Molecular mechanism study has identi ed that melatonin inhibits the mTOR signaling pathway through MT1 receptors in bovine mammary epithelial cells and via this pathway melatonin suppresses the synthesis of milk fat [50]. This observation provides a new basis for applying melatonin to regulate milk fat metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…BMECs were collected using 0.25% trypsin (Solarbio, Beijing, China) and lysed in RIPA buffer (Solarbio, Beijing, China) containing 1% PMSF (Pierce, Rockford, IL, USA). Western blot was carried out as described previously [5]. Primary antibodies against β-actin (mAbcam 8226) (1:2000, Abcam), Smad3 (C679H) (1:1000, Cell Signaling Technology), and HRP goat Anti-Rabbit IgG secondary antibody (ab97051) (1:2000, Abcam) were used.…”
Section: Western Blot Assaymentioning
confidence: 99%
“…Cow milk is a natural food with high nutritional benefits and is therefore considered as basic food in many diets. Milk fat is the main determinant of its nutritional value, and as such it is usually applied to indicate milk quality [1,2], and therefore its synthesis process has been widely studied [3][4][5]. Milk fat synthesis is influenced by several factors, such as heredity, hormone, physiology, environment, and nutrition [6][7][8], but the understanding of the regulation mechanism of milk fat synthesis is still minimal.…”
Section: Introductionmentioning
confidence: 99%